Analisis Struktur Ekonomi dan Struktur Perkotaan dalam Mencapai Good Governance City (Studi Kasus pada Kota Kupang) - Yudith F. Lerrick; Boy S. Efendi (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2021)
Economic structure based on the role of various economic business fields in producing goods and services will determine the economic structure of a region. The economic structure that is formed from the added value created by each business field illustrates how much dependence of an area on the ability to produce Dario each business field. The value of the per capita PDRB of Kupang City on the basis of prices in effect from 2015 to 2019 is constantly increasing. In 2015 the per capita PDRB was recorded at 42.69 million rupiah. Normally, it continues to increase until 2019 reaching 56.46 million Rupiah. This high increase in per capita PDRB is due to the inflation factor which is in accordance with Article 33 UUD 1945 Constitution which has been amended four times. This also affects the urban structure, wherein Perpres No. 55 of 2011 concerning National Spatial Planning (RTRW). Therefore, infrastructure planning is good to produce good and quality infrastructure development, it is necessary to have a workshop in order to provide an understanding of all elements related to leading to good governance city.